Conformational disorder in a hybrid 2D perovskite with a long aliphatic chain under pressure - Lekina, Yulia (2023)
Two-dimensional hybrid lead halide perovskites are important materials for solar energy and optoelectronic applications. Although the inorganic component normally determines the electronic structure, there has been an emerging interest in organic sublattice engineering. The organic spacer can influence the stability, the mechanical and optoelectronic properties, and the device performance, at least through steric effects. Order-disorder transitions facilitated by the organic molecules are some of the pathways that mediate this influence. Herein, we investigated the effect of hydrostatic pressure on the optical properties of hexadecylammonium (HDA) lead iodide ((HDA)2PbI4), where the pliable organic part contains a long aliphatic chain with many conformational degrees of freedom, by means of optical, Raman, and solid-state NMR spectroscopy, as well as density functional theory simulations. Under moderate pressures of 2 GPa and above, the perovskite crystal exhibits domains with differing photoluminescence (PL) energies. The PL peak distribution exceeds 100 nm at higher pressure, and the changes are partly irreversible after pressure release. We explain the observed phenomena by conformational transitions, which occurred around the different C-C bonds proximate to the cationic NH3 end HDA and affected the lead iodide nanosheets and thus the optoelectronic properties. The micrometer-scale bandgap junctions formed in one material can be applied in novel optoelectronic devices.